ECONOMIC TRAINING OF JUNIOR SPECIALISTS OF SPHERE OF COOPERATION: MODEL AND ITS REALIZATION - Stebljuk, Svitlana V. (Educological discourse, 2014)
In the article a concept of economic training is examined and the interpretation of economic training of future junior specialists in the cooperation sphere is formulated. Such constituents of training are mentioned: economic education and economic upbringing. The model of economic training of specialists as far as components, indexes, is analyzed and levels are specified. The purpose of this model is to provide the realization of pedagogical terms of economic training of future junior specialists in the cooperation sphere. Methodological approaches are selected: systematical, synergistic, personality and activity oriented. The results of this pedagogical experiment are given in relation to efficiency of the offered model.